Pelargonidin-3-O-Glucoside Encapsulated Pectin-Chitosan-Nanoliposomes Recovers Palmitic Acid-Induced Hepatocytes Injury - Naymul Karim; Mohammad Rezaul Islam Shishir; Yuting Li; Ould Yahia Zineb; Jianling Mo; Jitbanjong Tangpong; Wei Chen (MDPI AG, 2022)
Pelargonidin-3-O-glucoside (Pg) is a well-known anthocyanin derivative possessing potential biological activity. Nonetheless, the bioactivity of Pg is limited due to instability in the physiological environment. Functionalized nanoliposomes using chitosan and/or pectin coating is an excellent carrier system for nanoencapsulation of food bioactive compounds such as Pg. Therefore, this study aimed to investigate the protective effect of Pg-loaded pectin-chitosan coated nanoliposomes against palmitic acid (PA)-induced hepatocytes injury in L02 cells. Firstly, Pg-loaded pectin-chitosan coated nanoliposomes were characterized using the DLS, HPLC, TEM, and cellular uptake study in L02 cells. Thereafter, we assayed the protective effect against PA-induced lipotoxicity, ROS and O2•− generation, mitochondrial dysfunction (MMP), and GSH depletion. Results showed that Pg-loaded nanoliposomes significantly reduced the PA-induced L02 cells toxicity via suppressing ROS production, O2•− generation, MMP collapse, and GSH reduction, whereas the free-Pg samples were not effective. On the contrary, the chitosan and/or pectin coated nanoliposomes showed higher results compared to coating-free nanoliposomes. Altogether, the results of our study ensured that Pg-loaded pectin-chitosan coated nanoliposomes was capable of reducing PA-induced hepatocytes injury. Thus, pectin-chitosan coated nanoliposomes can be useful for hepatocellular delivery of hydrophilic compounds with greater biological activity.